MEMBANGKITKAN RASA GIGIH DALAM BELAJAR UNTUK MENJADI SISWA BERKUALITAS MELALUI CERPEN “WUJUD PENDIDIKAN INDONESIA” KARYA DEVILLA ARDRAILSA TANDI DENGAN KAJIAN OBJEKTIF DAN PENDEKATAN HERMENEUTIKA - Tasya Amelia Saragi; Sri Syahputri; Mieke Angelika Siburian; Erika Cyntia Pebryanti Silitonga; Sani Hutabarat; Dhea Amalia; Rosmawaty Harahap (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This research seeks to examine a short story "Wujud Pendidikan Indonesia" by Devilia Ardrailsa Tandi, in a short story there are words that are interesting to analyze, researchers try to find intrinsic elements and meanings contained in short stories. Analyzing the content of short stories by reading and understanding repeatedly each paragraph listed. The type of analysis used is qualitative by applying descriptive methods, namely describing the results of the analysis through objective and hermeneutic approaches. It can help researchers in analyzing the content of short stories. The objective approach is a literary approach that prioritizes the intrinsic aspects of the literary work in question. Such as focusing on finding intrinsic elements which include theme, character/character, plot, setting, point of view, language style, and mandate in it. Meanwhile, the Hermeneutic approach is an approach that wants to find out other meanings or symbols described by words. Of course, in finding this approach, researchers must know the content contained in literary works, so that readers can enjoy literature and capture the messages conveyed by the author. Keyword: Objective, Hermeneutics, Short Story, Meaning